SIMULATION AND OPTIMIZATION OF ENERGY AND DAYLIGHTING PERFORMANCE IN GOVERNMENT DISTRICT OFFICE BUILDING IN THE TROPICS - Muhammad Rofi; Atthaillah Atthaillah; Erna Muliana; Nik Mohd Faiz Nik Kamrulzaman; Muhammad Iqbal (Arsitekno, 2026)
The increase in energy consumption in buildings, particularly in the government sector, poses a serious challenge in the effort to mitigate climate change. This research aims to analyze and optimize the facade design of the Aceh Utara district office building to improve energy efficiency through an integrative approach between reducing the overall thermal transfer value (OTTV) and utilizing daylighting based on useful daylight illuminance (UDI) metric. The simulation is conducted using Rhinoceros (RH) software integrated with Grasshopper (GH) to evaluate the combination of design variables such as window-to-wall ratio (WWR), depth, and angle of external shading. Validation of the OTTV value refers to the official calculator from the Government Department Public Works and Public Housing (PUPR), while the daylighting simulation utilizes annual climate data to obtain lighting distribution in three categories: insufficient, optimal, and excessive. The research results show that opening and shading optimization strategies can reduce OTTV to below the threshold of 35 W/m² according to SNI 6389:2020, as well as increase the proportion of areas with optimal daylighting. These findings underscore the importance of an integrative approach to energy and daylighting performance in facade design, and demonstrate the significant potential of climate-based daylight simulations to support the achievement of sustainable and energy-efficient government office buildings.